Handbook on Information Technologies for Education and Training 2008
DOI: 10.1007/978-3-540-74155-8_5
|View full text |Cite
|
Sign up to set email alerts
|

Ambient Intelligence and Ubiquitous Computing

Abstract: Ambient intelligence and ubiquitous computing characterize intelligent, pervasive and unobtrusive computer systems embedded into human environments, tailored to the individual's context-aware needs. Such miniaturised modern information and communication technology (ICT) supports humans by offering information and guidance in various application areas. Ambient intelligence leads to ambient learning by embedding individual learning activities in every day life. The learners participate and co-operate in, for exa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 26 publications
0
8
0
Order By: Relevance
“…The extensive possibilities for data collection and analysis provided by a sensor-based system enable the invisible and potentially permanent tracking of employees' activities (Bick & Kummer, 2008). These capabilities can cause employees to worry about permanent surveillance, to feel exposed, and to feel their privacy is violated (Barkuus & Dey, 2003;Garfinkel et al, 2005), as nearly all activities, including those that occur during breaks, become transparent.…”
Section: Effects Of Anxiety On the Usage Intentionmentioning
confidence: 99%
“…The extensive possibilities for data collection and analysis provided by a sensor-based system enable the invisible and potentially permanent tracking of employees' activities (Bick & Kummer, 2008). These capabilities can cause employees to worry about permanent surveillance, to feel exposed, and to feel their privacy is violated (Barkuus & Dey, 2003;Garfinkel et al, 2005), as nearly all activities, including those that occur during breaks, become transparent.…”
Section: Effects Of Anxiety On the Usage Intentionmentioning
confidence: 99%
“…• the rise of mobile devices and computing and, later, the emergence of Pervasive Computing (Bick and Kummer, 2008;Krumm, 2009;Satyanarayanan, 2001;Weiser, 1991) • the increasing need for adaptive, particularly user-adaptive (i.e., personalised) software systems (Brusilovsky et al, 2007;Salehie and Tahvildari, 2009;Schneider-Hufschmidt et al, 1993).…”
Section: Abelson and Sussmanmentioning
confidence: 99%
“…For instance, in the e-learning domain, it is already demonstrated that personalised computer-based instruction is superior to the traditional approaches (Kadiyala and Crynes, 1998). In other words, the pervasive computing vision manifests an unobtrusive, anytime and anywhere (Bick and Kummer, 2008) user experience which requires expansion of the personalisation era to the context-awareness era. In this regard, the computing paradigm has changed from user-computer perspective to context-computing setting perspective.…”
Section: Abelson and Sussmanmentioning
confidence: 99%
See 1 more Smart Citation
“…It is reasonable to say that in the sense of hardware technologies we already achieved a lot by considering the advancements in the networking technologies, computing power, miniaturization, energy consumption, materials, sensors etc. [2]. However pervasive computing is not just about developing such small computing residents for the real life, variety of applications exploiting such extended hardware infrastructure are the other side of the coin.…”
Section: Introductionmentioning
confidence: 99%